Peer review of cancer multidisciplinary teams: is it acceptable in Australia?. Issue 3 (16th February 2015) - Slavova‐Azmanova, Neli S; Johnson, Claire E; Platell, Cameron; Bydder, Sean; Saunders, Christobel M
Abstract: Objective: To develop a peer‐review model for assessment and quality improvement of cancer multidisciplinary teams (MDTs) and qualitatively assess its feasibility and acceptability in Australia. Design, setting and participants: A peer‐review methodology was developed, based on the United Kingdom's National Health Service peer‐review model and a comprehensive literature review. This was pilot tested in three mature MDTs in different settings. Semi‐structured interviews were conducted between December 2012 and July 2013 with all five peer reviewers and 17 MDT members. Thematic analysis was undertaken using a framework approach. Results: Peer reviewers and MDT members found the process reasonable, constructive and useful; however, those involved in the preparation for the review found it time‐consuming. Most MDT members considered the final report accurate and reflective of their service. Recommendations in the report were met with mixed reactions: several MDT members perceived some recommendations to be particularly relevant, while others viewed the same recommendations as impractical or of limited value. Many participants were unsure if recommendations would be fully implemented. The majority saw value in the process and expressed support for its implementation locally and nationally; however, feedback suggests the most appropriate format is yet to be established. Conclusions: Peer review of cancer MDTs is feasible and acceptable. We describe valuable lessons learnt and recognise that further development of the proposed peer‐review model and national benchmarking of MDTs against established outcome measures is required if this process is to be widely implemented.